Histological stroke clot analysis after thrombectomy: Technical aspects and recommendations. Issue 5 (July 2020) - Staessens, S; Fitzgerald, S; Andersson, T; Clarençon, F; Denorme, F; Gounis, MJ; Hacke, W; Liebeskind, DS; Szikora, I; van Es, ACGM; Brinjikji, W; Doyle, KM; et al.
The recent advent of endovascular procedures has created the unique opportunity to collect and analyze thrombi removed from cerebral arteries, instigating a novel subfield in stroke research. Insights into thrombus characteristics and composition could play an important role in ongoing efforts to improve acute ischemic stroke therapy. An increasing number of centers are collecting stroke thrombi. This paper aims at providing guiding information on thrombus handling, procedures, and analysis in order to facilitate and standardize this emerging research field.